2007
DOI: 10.1063/1.2760042
|View full text |Cite
|
Sign up to set email alerts
|

Controlled formation of metallic nanoballs during plasma electrolysis

Abstract: Formation of spherical nanoparticles ͑hereafter "nanoballs"͒ in a gas/liquid mixed dual phase system during plasma electrolysis is reported. A gas/vapor sheath is formed at the electrode/ electrolyte interface when the applied voltage is high enough to induce discharge plasma. Through this nonequilibrium process, the authors have produced Ni, Ti, Ag, and Au metallic nanoballs from the cathode mother materials with a certain size controllability. The electrode surface is partially melted by the local current co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
99
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 25 publications
(27 reference statements)
0
99
0
3
Order By: Relevance
“…In this solution plasma technique [19][20] , an electrode was used as the raw material for the preparation of nanocrystals. Various nanoparticles such as Ni 19,20 , Au 20,21 , ZnO 22 have been synthesized via solution plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this solution plasma technique [19][20] , an electrode was used as the raw material for the preparation of nanocrystals. Various nanoparticles such as Ni 19,20 , Au 20,21 , ZnO 22 have been synthesized via solution plasma.…”
Section: Introductionmentioning
confidence: 99%
“…In this solution plasma technique [19][20] , an electrode was used as the raw material for the preparation of nanocrystals. Various nanoparticles such as Ni 19,20 , Au 20,21 , ZnO 22 have been synthesized via solution plasma. In general, the solution plasma technique offers many advantages, such as (1) simple experimental setup, (2) no requirement for gas supply, (3) higher productivity than conventional solution processes, and (4) applicability to mass production.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Recently, a solution plasma has been applied to the synthesis of nanoparticles. The produced particle size and compositions were affected by the plasma conditions, such as the electrode shape, 16,17 voltage, 18,19 atmospheric pressure, 20 and material. 21 Previous reports indicated that the shape of the electrode affects the plasma conditions and obtained nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The product obtained after plasma electrolysis was found to be uniformly shaped spherical nanoparticles called 'nanoballs'. [1] As a result of glow-discharge plasma causing localised melting spots on the cathode surface to occur repeatedly, molten material in order of nanosize became ejected from the cathode. Then they solidified into spherical nanoballs because of the surface tension and quenching effect of the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Then they solidified into spherical nanoballs because of the surface tension and quenching effect of the electrolyte. [1,2,8] Nanoballs have good potential as photocatalytic materials because of their very small size and therefore high reactivity. Titanium oxide (TiO 2 ) and zinc oxide (ZnO) are wellknown photocatalytic/photoelectric materials.…”
Section: Introductionmentioning
confidence: 99%